KERJASAMA ASEAN POWER GRID DALAM MENINGKATKAN KETAHANAN LISTRIK DI INDONESIA - Andreas Said; Den Yealta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study is an international political economy study discussing ASEAN Power Grid (APG) cooperation in increasing electrical resilience in Indonesia. This study aims to identify and impact APG cooperation in improving the electrical resistance of Indonesia. Indonesia is one of the countries with the largest electricity consumption in the world and number 1 in southeast asia. Where electricity becomes a basic necessity in everyday life as well as in the development of the country.APG is a cooperation formed by all ASEAN members to improve electrical security and connect electricity to all member countries, as electricity becomes one of the basic needs that its availability is needed, APG also become a forum for private parties in improving the economy and also help the country in selling electricity supply, as well as a motivator for each country to improve domestic electrical resistance.the increase of electrical resistance which is the objective of APG cooperation, requires Indonesia to cooperate with neighboring countries such as Malaysia and Singapore to implement the principal of cooperation is the buying and selling of electricity through transmission lines built together based on MoU APG.In this case the authors use Noe-liberalism perspectives, supported by the theory of international cooperation and the concept of role and level of corporate analysis as an actor. The concept leads to qualitative methods and literature studies as a source of information..Keywords: Role, ASEAN Power Grid (APG), Electrical security, Electricity rate